POTRET MASYARAKAT URBAN DALAM NOVEL METROPOP SAY NO TO ME KARYA WIWIEN WINTARTO - Darma, Tesa; Hasanuddin WS, Hasanuddin WS (Universitas Negeri Padang, 2019)
This study aims to describe the representation of: (1) individualist, (2) recreation lifestyle, (3) mobility lifestye, (4) instant lifestyle, and (5) virtual lifestyle of urban societies in novel metropop Say No to Me by Wiwien Wintarto. Data of this researchÂ is element of novel metropop Say No to Me by Wiwien Wintarto. The source of this research data is novel metropop Say No to Me by Wiwien Wintarto. There are four stages to collect the data. First, reading novel metropop Say No to Me by Wiwien Wintarto. Second, literature review. Third, find and write the data related to research problem. Based on result of the study concluded: (1) urban societies are individualist, (2) urban societies need recreation, (3) the level of urban societies mobility is high, (4) urban societies want their needs to be obtained instantly, and (5) urban societies depend on Information Technology (IT).Keywords: urban societies, metropop novel, individualist, mobility, instant, virtual